2022
DOI: 10.1177/17474930221107500
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of posterior circulation stroke: Acute management and secondary prevention

Abstract: One fifth of strokes occur in the territory of the posterior circulation but their management, particularly acute reperfusion therapy and neurointervention procedures for secondary prevention, have received much less attention than similar interventions for the anterior circulation. In this review we overview treatment of posterior circulation stroke, including both interventions in the acute setting and, secondary prevention. We focus on areas in which management of posterior circulation stroke differs from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 59 publications
1
13
0
1
Order By: Relevance
“…The evidence to support the benefit of endovascular therapy in patients with basilar artery occlusion has only been demonstrated recently. 24,25 Two prior multicenter randomized trials did not detect favorable outcomes in BAO patients receiving EVT compared with those receiving standard medical therapy. 5,6 Two multicenter, registry studies suggested the benefit of EVT for BAO patients.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence to support the benefit of endovascular therapy in patients with basilar artery occlusion has only been demonstrated recently. 24,25 Two prior multicenter randomized trials did not detect favorable outcomes in BAO patients receiving EVT compared with those receiving standard medical therapy. 5,6 Two multicenter, registry studies suggested the benefit of EVT for BAO patients.…”
Section: Discussionmentioning
confidence: 99%
“…2 Our second review in this issue provides the latest data on management of posterior circulation stroke, both acute and secondary prevention. 3 It highlights the results from two recent trials of thrombectomy presented in May at the European Stroke Congress 2022, which both showed that thrombectomy was highly effective for BAO. 4 ATTENTION (EndovAscular TreaTmENT for acute basilar artery occlusION), the protocol paper of which is also published in this issue, 5 recruited patients within 0–12 h from the estimated time of stroke onset in China.…”
mentioning
confidence: 86%
“…These dysfunctions interfere with the patient's independent performance of daily activities. As a result, patients experience deterioration of activity, damage of autonomy, interpersonal relationship problem, leading to long-term depression, anxiety, and psychosocial maladjustment [3,4].…”
Section: Introductionmentioning
confidence: 99%